Measurement of electron beam energy characteristics at an industrial accelerator - Pomatsalyuk, R.I.; Shevchenko, V.A.; Shlyakhov, I.N.; Tenishev, A.Eh.; Titov, V.Yu.; Titov, D.V.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2017)
At an electron accelerator, the particle energy is one of critical parameters in the technological processes, as well as when conducting the radiation tests. The report presents the results of modernization of beam energy-spectrum analyzer on the basis of a 90˚ electromagnet of an industrial Linac LU-10 (10 MeV, 10 kW). A control system on the basis of a multifunction USB device for the analyzer data acquisition and processing has been developed. The results of measuring the energy characteristics of the accelerator beam with the analyzer, as well as using a dosimetric wedge technique are presented. A computer simulation method was used to study the features of the wedge application in case of a beam with wide spectrum. The conditions of on-line electron energy control using a wide-aperture stack monitor are investigated. A comparative analysis of results of the energy determination by the different techniques is carried out. Енергія випромінення є одним з критичних параметрів у радіаційно-технологічних процесах, а також при проведенні випробувань на прискорювачах електронів. У статті викладені результати модернізації аналізатора спектра пучка промислового прискорювача ЛУ-10 (10 МеВ, 10 кВт) на основі 90˚-електромагніта. Для прийому і обробки даних розроблена система контролю з використанням багатофункціонального USB-пристрою. Приведені результати вимірювання енергетичних характеристик пучка прискорювача за допомогою аналізатора, а також дозиметричного клину. Методом комп'ютерного моделювання вивчені особливості застосування клину у тому разі, коли пучок з широким спектром. Досліджені умови on-line контролю енергії електронів з використанням широкоапертурного стек-монітора. Проведено порівняльний аналіз результатів вимірювання енергій, отриманих різними методами. Энергия излучения является одним из критических параметров в радиационно-технологических процессах, а также при проведении радиационных испытаний на ускорителях электронов. В статье изложены результаты модернизации анализатора спектра пучка электронов на основе 90˚-электромагнита промышленного ускорителя ЛУ-10 (10 МэВ, 10 кВт). Для приема и обработки данных разработана система контроля с использованием многофункционального USB-устройства. Приведены результаты измерения энергетических характеристик пучка ускорителя с помощью анализатора, а также дозиметрического клина. Методом компьютерного моделирования изучены особенности применения клина в случае пучка с широким спектром. Исследованы условия on-line мониторинга энергии электронов с использованием широкоаппертурного стек-монитора. Проведен сравнительный анализ результатов измерения энергии, полученных разными методами.